Short‐term vegetation recovery after alien plant clearing along the Rondegat River, South Africa. Issue 3 (22nd October 2017) - Fill, Jennifer M.; Kritzinger‐Klopper, Suzaan; van Wilgen, Brian W.
Abstract : The outcomes of ecosystem restoration projects should be periodically monitored to inform subsequent adaptive management decisions. In 2012, a project was begun to remove both invasive alien plants and fish from the Rondegat River in South Africa. Although the initial post‐intervention dynamics of aquatic fauna have been documented, the results of the simultaneous clearing of dense riparian stands of alien trees and shrubs have not been reported. We examined native riparian vegetation recovery over 3 years after alien plant clearing. We documented increased cover of native riparian shrubs, but a simultaneous increase of alien and native weedy grass cover. Secondary invasions, especially by grasses, can have strong effects on ecosystem dynamics and achieving the goals of restoration may therefore require additional active management. Our findings provide an initial baseline reference for future monitoring and adaptive management decisions.